Some Important Plants for Epilepsy Treatment: Antioxidant Activity and Flavonoid Compositions - Gür, Mahmut; Güder, Aytaç; Verep, Didem; Güney, Kerim; Özkan, Osman E.; Seki, Nagihan; Kandemirli, Fatma (Springer Science and Business Media LLC, 2017)
Epilepsy, a disorder of the brain, is a major health problem that the widespread availability and use of herbal medicines raise the potential for adverse effects in the epilepsy population. Although many synthetic antiepileptic drugs are available in operation, their efficiency does not verify with the all population suffering from this disorder because of the major restrictions such as side effects and the drug interactions in its clinical utility. This paper is concerned with antioxidant activity, total phenolic and flavonoid contents and flavonoid composition of the 14 plants for three different solvents (water, ethanol and hexane). For this reason, FRAP, DPPH free radical scavenging, metal-chelate and H2O2 scavenging activities were investigated. In addition, total phenolic and flavonoid contents of extracts were determined via spectroscopic techniques. Lastly, composition of catechin, epicatechin, rutin, naringin, myricetin, luteolin, naringenin and apigenin was found with normal-phase HPLC in the obtained extracts. Extracts of fourteen plants taxa foreseen in having antioxidant and antiepileptic features were obtained with soxhlet extraction using different solvents, i.e., water, ethanol and hexane in this study. The extracts of 14 plant taxa were acquired: French lavender (Lavandula stoechas L.—inflorescence), Valerian (Valeriana officinalis L.—herb), Syrian rue (Peganum harmala L.—seeds), Liquorice (Glycyrrhiza glabra L.—roots), Boxwood (Buxus sempervirens L.—leaves), Chicory (Cichorium intybus L.—herb), Marjoram (Origanum majorana L.—leaves), Lemon balm (Melissa officinalis L.—leaves), Prickly juniper (Juniperus oxycedrus L.—fruits), Wild camomile (Anthemis cotula L.—flowers), Oats (Avena sativa L.—herb), Coriander (Coriandrum sativum L.—seeds), Flax (Linum usitatissimum L.—seeds) and Marijuana (Cannabis sativa L.—seeds)”. The antioxidant capacities of plant extracts were assayed with four different assays including FRAP, metal chelating, H2O2, DPPH scavenging because the antioxidant capacity cannot be fully described by a single method. The determined flavonoid amounts are between 3.85 and 694-47 (catechin), 2.70 and 2045.49 (epicatechin), 0.12 and 47.11 (rutin), 0.02 and 24.99 (naringin), 0.80 and 153.19 (myricetin), 0.03 and 7.80 (luteolin), 0.02 and 4.75 (naringenin) and 0.38 and 2.73 (apigenin) as µg g−1 plant. These plant materials and their flavonoid components via gamma-aminobutyric acid (GABA) and GABAA receptors can be therapeutical due to their different mechanism on treatment of epilepsy.
Keywords: Epilepsy; Medicinal plants; Phenolic; Flavonoid; HPLC; Antioxidant; 6. Clean water; 3. Good health